EFFECTS OF PRODUCER PRICE INDEX MOVEMENTS ON FINANCIAL PERFORMANCE OF SMALL AND MEDIUM SUPERMARKETS IN MOSHI MUNICIPALITY - Kisava, Paul; Majondo, Safari; Komba , Ladis (Community Development Journal, 2025)
Small and Medium Enterprises (SMEs), particularly supermarkets in Tanzania, have experienced persistent financial pressures from rising input costs driven by fluctuations in the Producer Price Index (PPI). In Moshi Municipality, these increases have intensified operational costs, reduced profitability, and threatened long-term sustainability. This study aimed to determine the effects of PPI movements on the financial performance of small and medium supermarkets. Anchored in the Cost-Push Inflation Theory, a convergent parallel mixed-methods design was applied, integrating quantitative and qualitative approaches for comprehensive analysis. The target population comprised 450 small and medium supermarkets employees, with a sample size of 212 respondents, including managers, owners, cashiers, and storekeepers, selected through simple random and purposive sampling. Data were collected using structured questionnaires, in-depth interviews, and financial performance reports from 2020–2024. Instrument validity was ensured through expert review, while reliability tests yielded Cronbach’s Alpha values between 0.72 and 0.78. Quantitative data were analyzed using descriptive statistics (frequencies, percentages, means, and standard deviations) and multiple regression in SPSS version 27, while qualitative data were examined through contextual analysis, with coding and categorization to identify emerging themes. Findings revealed that demand constraints (Beta = 0.648, p < 0.001) were the strongest predictors of financial performance, whereas PPI cost pressures alone were not statistically significant. Nonetheless, descriptive results indicated that PPI increases indirectly constrained financial outcomes by raising operational costs, reducing product variety, and forcing operational cutbacks. Adaptive strategies such as innovation, quality improvement, and cost optimization were widely adopted to mitigate inflationary shocks. The study concludes that while demand-side factors predominantly influence supermarket performance, PPI movements necessitate operational adjustments critical for resilience. It recommends investment in inventory management technologies, strategic sourcing, and policy measures such as tax reliefs and subsidized supply chains.